APLIKASI MENGETAHUI TEMBANG MACAPAT JAWA BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - Song Macapat Java is Indonesia's culturalheritage , which is now one song areas in Indonesiaand became one song a wealth of evidence of theIndonesian nation . But this time the sources ofliterature regarding macapat Java is increasinglyminimal and hard to come by . One source is a Javalibrary macapat macapat book Java , which is acollection of saris or the contents of macapat Java . Theuse of technology to support activities in carrying outdaily activities is very common for some people . This isbecause some Mobile already has the functionality andcapability more than just basic functions. Android as anoperating system that can be embedded in mobiledevices have the ability to be able to install applicationsthat are required by the user . In this thesis developedJava application macapat know , it is expected thatusers use mobile devices based on the Androidoperating system can be helped to learn and seekinformation macapat.Keywords : Android , Java macapat